2001
DOI: 10.1046/j.1523-1755.2001.59780102.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbamoylation of amino acids and proteins in uremia

Abstract: Cyanate spontaneously transformed from urea increases as renal function decreased. Acting as a potential toxin, the active form of cyanate, isocyanic acid, carbamoylates amino acids, proteins, and other molecules, changing their structure, charge, and function. The resulting in vivo carbamoylation can modify the molecular activity of enzymes, cofactors, hormones, low-density lipoproteins, antibodies, receptors, and transport proteins. Antibodies specific for epsilon-amino-carbamoyl-lysine (homocitrulline) loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(105 citation statements)
references
References 25 publications
2
95
0
2
Order By: Relevance
“…It has been suggested that urea might be a uremic toxin because cyanate, which forms spontaneously from urea, is elevated in chronic renal failure, resulting in increased protein carbamylation (17). The present studies add to the evidence that urea is a uremic toxin, given our observation that protein carbonylation is increased over the range of urea concentration that occurs in chronic renal failure (Fig.…”
Section: Proteins Are Extensively Carbonylated In Normal Mouse Renal supporting
confidence: 70%
See 1 more Smart Citation
“…It has been suggested that urea might be a uremic toxin because cyanate, which forms spontaneously from urea, is elevated in chronic renal failure, resulting in increased protein carbamylation (17). The present studies add to the evidence that urea is a uremic toxin, given our observation that protein carbonylation is increased over the range of urea concentration that occurs in chronic renal failure (Fig.…”
Section: Proteins Are Extensively Carbonylated In Normal Mouse Renal supporting
confidence: 70%
“…2A), indicating that high urea does cause oxidative damage to proteins. Cyanate, which forms spontaneously from urea, can modify proteins by carbamylating them (17). To assess the possibility that urea-induced carbonylation might be an indirect effect of cyanate-induced carbamylation, we used an ion-exchange resin to remove cyanate from the urea solutions that we used (see Materials and Methods).…”
Section: High Urea Causes Single-strand Breaks In Dna and 8-oxoguaninementioning
confidence: 99%
“…The cyanate thus formed can become protonated and form isocyanic acid, which reacts with available α-and ε-NH 2 groups of proteins, resulting in the formation of a carbamylated polypeptide [51]. The strong correlation between protein carbamylation and renal disease is intuitive from this perspective and, in fact, several targets of carbamylation have been demonstrated in patients with renal failure, including free amino acids, plasma proteins, leucocyte proteins and haemoglobin [52][53][54][55][56][57][58][59][60][61][62]; however, the carbamylation of lipoproteins is most relevant to atherogenesis. In CKD patients, carbamylation of LDL has been identified as a novel risk factor for CVD and a biomarker for atherogenic progression [2].…”
Section: Ckd and Protein Carbamylationmentioning
confidence: 99%
“…Thus, uraemia secondary to renal diseases is a pathological state that leads to the formation of isocyanate. 7 The second key reactant for isocyanate formation is thiocyanate (SCN − ), a metabolite of cyanide that is present in cigarette smoke. Thiocyanate increases in urine, serum and saliva with the amount of cigarette smoke.…”
Section: Introductionmentioning
confidence: 99%